Impact of a culturally adapted digital literacy intervention on older people and its relationship with health literacy, quality of life, and well-being - Carrasco-Dajer, Claudia Marisol; Vera-Calzaretta, Aldo Renato; Ubillos-Landa, Silvia; Oyanedel, Juan Carlos; Díaz-Gorriti, Virginia (Frontiers in Psychology, 2024)
A study was conducted with pre-and post-evaluation of a digital literacy (DL) intervention in people aged 60 years and over. A total of 56 participants (experimental group N=32 and control group N=24) were recruited for convenience in community centers. The intervention was adapted to the needs of the participants, there were five face-to-face sessions and remote reinforcement for three months, carried out by trained university students for five months. Sociodemographic variables such as self-perception of socioeconomic level and education, among others, were evaluated. The impact was assessed using the digital literacy scale (MDPQ16), indicators of frequency and types of internet and mobile phone use, health literacy (SAHLSA and NSV), quality of life (SF-12), hedonic well-being (Diener's SWLS and Cummins' PWI) and perceived social support using the Zimet scale. The intervention had a significant impact with an effect size of r=.27 on digital literacy, separate t-test comparisons revealed a markedly significant change for digital literacy in the experimental group, before and after the pre-post t-test(31) = 3.56, p = .001, but not in the control group, t(23) = .082, p =.93. No direct impact on health literacy, health-related quality of life, and hedonic well-being was identified. We examined the indirect impact of change in digital literacy and found that it correlated with improvements in well-being and social support, as well as quality of life. Using the reliable change score from Jacobson & Truax (1991), individuals with significant changes were detected and compared with those who did not change.Evaluation that contributes by identifying elements for improvement in future interventions and discusses the importance of culturally adapting continuing education in older people.